A new criterion for peak shear strength of rock joints based on shear-direction-related morphology description - Song, Yu (Frontiers in Materials, 2025)
Accurate characterization of joint roughness relative to shear direction is crucial for predicting the peak shear strength (τp) of rough rock joints. This study proposes a modified peak shear strength criterion based on shear-direction-dependent morphological parameters. Artificial fractal joints and natural sandstone tension joints with varying roughness were replicated using 3D printing and cast in cement-based materials. Direct shear tests under constant normal load (CNL) conditions were conducted to quantify the mechanical behaviors of rough joints. Joint morphology was characterized using statistical values (mean μ, standard deviation σ) of the apparent dip angle (θ*) distribution along the shear direction. A parameter E (θ*|θ*>0°)-μ, representing the conditional expectation of positive apparent dip angles relative to the shear direction, was proposed to effectively capture shear-direction-dependent roughness. A new τp criterion incorporating this parameter was established within a Mohr-Coulomb framework. Validation against experimental data and published studies demonstrates its improved accuracy, particularly for low-roughness joints, compared to existing criteria. This approach provides a physically meaningful and efficient method for estimating τp, enhancing stability assessments in rock mass engineering.